The antitumor effect of TAT-DCF1 peptide in glioma cells. (October 2018) - Wang, Jiao; Wang, Qian; Zhou, Fangfang; Li, Jie; Li, Qian; Zhou, Hong; Li, Shiman; Ma, Sujuan; Wen, Tieqiao
Abstract: Background: Glioblastoma is one of the most malignant brain cancer, thus, establishing an effective therapy is paramount. Our previous results indicate that dendritic cell-derived factor (DCF1) is an attractive candidate for therapy against Glioblastoma, since its overexpression in Glioblastoma U251 cells leads to apoptosis. However, the delivery approach limits its clinical application, in this paper, we expressed TAT-DCF1 fusion protein in E.coli in order to surmount its current delivery problems. Methods: The coding sequences of the different domains of DCF1 (full length, cytoplasmic, extracellular, 19-amino acid), together with the N-terminal transactivator of transcription (TAT) sequence, were amplified and subcloned into the bacterial expression vector pET30a(+) in order to produce (His)6 -tagged fusion proteins. Coomassie blue-stained SDS-PAGE and Western blotting identification showed that purity of the fusion proteins. Results: Immunofluorescence and flow cytometry show that U251 cells were efficiently transduced with the fusion proteins. Cell viability, proliferation, and migration assays suggest that the complete TAT-DCF1 fusion protein significantly decreased U251 proliferation and migration. Flow cytometry further reveals that TAT-DCF1 triggered cellular apoptosis. Conclusions: In conclusion, these findings suggest that the TAT-DCF1 fusion protein was efficiently transduced into Glioblastoma U251 cells and induced the antitumor effect and support further investigation into specific targeting and side effects of TAT-DCF1 during drug delivery. Highlights: U251 cells were efficiently transduced with TAT- DCF1 fusion proteins. TAT-DCF1 fusion protein inhibits proliferation and induces apoptosis of U251 cells. The full length TAT-DCF1 significantly reduces the migration rate of U251 cells.